2017
DOI: 10.18203/2349-2902.isj20174495
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors influencing conversion of laparoscopic cholecystectomy to open cholecystectomy

Abstract: Background: Gall stone disease is a common disease affecting human beings. Over the past two decades, laparoscopic cholecystectomy has become gold standard for the surgical treatment of gallbladder disease. The advantages of laparoscopic cholecystectomy over open surgery are a shorter hospital stay, less postoperative pain, faster recovery, better cosmoses. This study was planned to identify the circumstances and the risk factors influencing the conversion of laparoscopic cholecystectomy to open procedure.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Thyagarajan et al and Mukherjee et al11,13,14 Mean age of patients in present study was found to be 41.29 years which is comparable to the studies by Tariq et al, Singh et al and Mukherjee et al11,12,14 Maximum cases were in the age range of 41-50 years. Maximum rate of conversion i.e.…”
supporting
confidence: 84%
“…Thyagarajan et al and Mukherjee et al11,13,14 Mean age of patients in present study was found to be 41.29 years which is comparable to the studies by Tariq et al, Singh et al and Mukherjee et al11,12,14 Maximum cases were in the age range of 41-50 years. Maximum rate of conversion i.e.…”
supporting
confidence: 84%
“…In this study, we found that increase GB wall thickness on preoperative ultrasound which encountered in 39 patients out of 110 patients (35.5%) were associated with increase operative difficulty in 18 patients out of 39 patients, and our conversion rate to open surgery in six patients out of 110 patients (5.5%) was within the range reported by several other studies (1 -10%) as in Indian one conducted in 2017 with a report of conversion rate of 10% (16) , in USA in 2010 were the rate was 9% (17) , and a local study in Iraq in 2007 (18) where the rate was 5%. In this study, GB wall thickness significantly determines the difficulty during surgery.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is supported by Thyagarajan M et al They found a conversion rate of as high as 34% in cases with history of previous attacks of acute cholecystitis. 20 Liu et al and Khetan A also reported previous history of acte cholecystitis as a significant predictor of difficult LC. 21,22 Acute cholecystitis may lead to increased gall bladder wall thickness and cause scarring and fibrosis in and around gall bladder, making subsequent surgery difficult.…”
Section: Discussionmentioning
confidence: 94%